1988
DOI: 10.1172/jci113708
|View full text |Cite
|
Sign up to set email alerts
|

In vitro mutagenesis of HLA-B27. Substitution of an unpaired cysteine residue in the alpha 1 domain causes loss of antibody-defined epitopes.

Abstract: The HLA class I molecules identified serologically as HLA-B27 are highly associated with ankylosing spondylitis and related human disorders. All known HLA-B27 amino acid sequences contain a cysteine residue at position 67; no other published HLA class I sequence contains a cysteine within the hypervariable region of the a, domain, which extends from amino acid residues 63-84. To investigate the role of this cysteine residue in the antigenic structure of HLA-B27, we isolated a genomic clone encoding a molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 37 publications
(18 reference statements)
2
16
0
Order By: Relevance
“…After preincubation at 37°C the binding of the HLA-B27.Ser 67 aggrecan peptide tetramer was significantly reduced after 1 h suggesting that the staining of ILT-2-transfected cells strongly depends on the stability of the HLA-B27 complex. These findings are in line with the hypothesis that the stability of the molecule might have been altered by the mutation at position 67 of the HLA-B27 H chain (25), which might also be the reason for an abrogation of mAb recognition of HLA-B27 molecules after site-directed mutagenesis of residue 67 Cys to tyrosine (45,46).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…After preincubation at 37°C the binding of the HLA-B27.Ser 67 aggrecan peptide tetramer was significantly reduced after 1 h suggesting that the staining of ILT-2-transfected cells strongly depends on the stability of the HLA-B27 complex. These findings are in line with the hypothesis that the stability of the molecule might have been altered by the mutation at position 67 of the HLA-B27 H chain (25), which might also be the reason for an abrogation of mAb recognition of HLA-B27 molecules after site-directed mutagenesis of residue 67 Cys to tyrosine (45,46).…”
Section: Discussionsupporting
confidence: 86%
“…6). Its hydrophobic part forms van der Waals contacts to Tyr 7 and Ile 66 , while the charged guanidyl moiety is stabilized by a bifurcated salt bridge to Glu 45 and a hydrogen bond to Thr 24 . The side chain of Cys 67 (Fig.…”
Section: Impact Of Cys 67 For the Coordination Of Pr2 In The B Pocketmentioning
confidence: 99%
See 1 more Smart Citation
“…(Accepted for publication 25 July 1990) The association of ankylosing spondylitis with HLA-B27 was first described 17 years ago (Brewerton et al, 1973a;Schlosstein et al, 1973); the realization that other seronegative spondyloarthropathies, notably reactive arthritis, had the same association followed rapidly (Brewerton et al, 1973b), There has been an enormous increase in our understanding ofthe structure and function of HLA molecules in the intervening years: the amino acid sequence of several B27 variants is known (Choo et al, 1986) and there is a crystallographic picture of its likely threedimensional structure (Bjorkman et al, 1987); the B27 gene has been cloned (Szots et al, 1986), subjected to mutational analysis (Taurog & El-Zaatari, 1988) and expressed in transgenic mice Nickerson, Luthra & David, 1990), Furthermore, the function of class I MHC antigens in presenting antigenic peptides to T cells has been elegantly demonstrated (Townsend et al, 1986), It is rather frustrating, therefore, that despite this wealth of information, the involvement of B27 in the pathogenesis of these arthropathies remains shrouded in mystery.…”
Section: J S H Gaston Department Of Rheumatology University Of Bimentioning
confidence: 99%
“…Crystallographic studies have suggested that the amino acid sequence of the HLA-B27 antigen studied in this report corresponds to a part of the presumed antigen-peptide binding cleft (34, 35). Also, the possible role of the unpaired cysteine residue at position 67 in interacting with ligands has been suggested (20). All ofthese possibilities are not mutually exclusive.…”
Section: Resultsmentioning
confidence: 99%